A new and simple model for magneto-optics uncovers an unexpected spin switching. (26th October 2015) - Zhang, G. P.; Bai, Y. H.; George, Thomas F.
Abstract: In magneto-optics the spin angular momentum S z of a sample is indirectly probed by the rotation angle and ellipticity, which are mainly determined by the off-diagonal susceptibility . A direct and analytic relation between S z and is necessary and of paramount importance to the success of magneto-optics, but is often difficult to acquire since quantum mechanically the relation is hidden in the sum-over-states. Here we propose a new and simple model to establish such a much needed relation. Our model is based on the Hookean model, but includes spin-orbit coupling. Under continuous wave excitation, we show that is indeed directly proportional to S z for a fixed photon frequency ω . Such an elegant relation is encouraging, and we wonder whether our model can describe spin dynamics as well. By allowing the spin to change dynamically, to our surprise, our model predicts that an ultrafast laser pulse can induce a spin precession; with appropriate parameters, the laser can even reverse spin from one direction to another. This works for both the circularly and linearly polarized light. The spin reversal window is narrow. These unexpected results closely resemble all-optical helicity-dependent magnetic switching found in much more complicated ferrimagnetic rare-earth compounds. Therefore, we believe that our spin-orbit coupled model may find some important applications in spin switching processes, a hot topic in femtomagnetism.